Knowledge, Attitude and Dengue Preventive Behavior in Legok, Jambi City - Najmi Qalami Hadist; M. Ridwan; Budi Aswin; Dwi Noerjoedianto; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
Dengue Hemorrhagic Fever (DHF) is still a public health problem that requires household involvement in vector control. Legok Village in Jambi City has environmental characteristics and population density that have the potential to support dengue transmission. This study aims to analyze the relationship between knowledge and attitudes towards dengue prevention behavior in the community of Legok Village, Jambi City. Quantitative analytical research with a cross-sectional design was conducted in September 2025 on 235 respondents aged ≥17 years. Sampling was carried out in stages through random selection of RT clusters, then systematic random sampling at the household level. Data were collected using a structured questionnaire and analyzed univariate and bivariate with chi-square and Fisher exact tests. The results showed that 92.8% of respondents had poor dengue prevention behavior, 60.9% had poor knowledge, and 90.6% had a positive attitude. There was no meaningful relationship between knowledge and dengue prevention behavior (p=0.142) or between attitudes and dengue prevention behaviors (p=0.380). Relatively good knowledge and attitudes have not automatically encouraged specific, routine, and household-based prevention behavior. Interventions need to be directed at assisting household practices, community mobilization, and strengthening the supportive environment for dengue prevention.